The 'BlueScreen HC' assay as a decision making test in the genotoxicity assessment of flavour and fragrance materials. Issue 7 (October 2015) - Etter, Sylvain; Birrell, Louise; Cahill, Paul; Scott, Heather; Billinton, Nick; Walmsley, Richard M.; Smith, Benjamin
Highlights The genotoxicity of 70 flavour and fragrance substances was assessed using BlueScreen HC. Positive results are highly predictive of positive regulator-required in vitro assays. Negative results were highly predictive of negative in vivo results. A top 1 mM or 0.5 mg/ml dose maintains sensitivity and increases specificity. The assay can fill data gaps for materials with no/limited regulatory test data.